Trans-ethnic Mendelian randomization analysis of membranous nephropathy and peripheral artery disease with mediating effects of thrombomodulin - Juhong Pan; Xingyue Huang; Yueying Chen; Nan Jiang; Yuxin Guo; Shiyuan Zhou; Yao Zhang; Bo Hu; Qing Deng; Qing Zhou (Scientific Reports)
Abstract This study employed a trans-ethnic two-sample Mendelian randomization (MR) analysis to investigate the causal relationship between membranous nephropathy (MN) and peripheral artery disease (PAD). In European populations, MN exhibited a significant positive causal effect on PAD (discovery: OR = 1.040, P = 0.028; validation: OR = 1.028, P = 0.031), whereas no such association was observed in East Asians (P > 0.05). A two-step mediation analysis identified several proteins influenced by MN, including thrombomodulin (TM) (β = 0.031, P = 0.001), macrophage colony-stimulating factor 1 (MCSF1) (β = 0.239, P = 0.015), stem cell factor (SCF) (β = 0.028, P = 0.002), and tissue factor (TF) (β = 0.031, P = 0.001), while MN negatively affected interleukin-1β (IL-1β) (β=-0.049, P = 0.015) and hepatocyte growth factor (HGF) (β=-0.027, P = 0.005). Multivariable MR analysis confirmed that only TM had an independent positive causal effect on PAD (β = 0.225, P < 0.001), and mediation analysis further validated TM as a significant mediator in the MN-to-PAD pathway (Z = 2.823, P = 0.048). Sensitivity analyses detected no significant pleiotropy or heterogeneity, supporting the robustness of our findings. This study highlights crucial ethnic differences in MN-associated PAD risk and underscores the importance of population-specific research. TM may serve as a potential therapeutic target for PAD prevention in MN patients, particularly those of European ancestry, providing novel insights into kidney-vascular disease mechanisms.